Low-Malignant Schwannoma of the Cervix in Pregnancy: A Case Report and Literature Systematic Review - Giada M. ALMIRANTE; Francesco CANTATORE; Gianluca TACCAGNI; Massimo CANDIANI; Massimo ORIGONI (Case Reports in Obstetrics and Gynecology)
Primary cervical melanocytic schwannomas, arising from the sympathetic chain, are very rare pigmented neural sheath tumors that, both grossly and clinically, are often misdiagnosed with other more frequent lesions of the uterine cervix. Literature review accounts for seventeen published cases of schwannomas of the cervix, ten of which are malignant and seven benign. Pathological examination with immunostaining techniques is essential for the correct diagnosis of these tumors. We report a case of primary cervical schwannoma in a 32-year-old female who was referred to our department at 13 weeks of gestation with a diagnosis of malignant melanoma of the cervix. Pathological review detailed a neoplasm with a myxoid spindle cell component and a minority of small epithelioid cells, with a low-malignant potential proliferation index: morphological and immunocytochemical findings were compatible with the diagnosis of nerve sheath tumor, type schwannoma. The patient underwent a vaginal trachelectomy and a prophylactic Shirodkar’s cerclage. Pregnancy was carried on without any negative event. The patient delivered by a caesarean section a healthy female newborn. Placental histology was negative. After 6 years from the first diagnosis, the patient is healthy and disease free.